Hypocalcemia in Military Casualties From Point of Injury to Surgical Teams in Afghanistan. (25th January 2021) - Conner, Jeffrey R; Benavides, Linda C; Shackelford, Stacy A; Gurney, Jennifer M; Burke, Edward F; Remley, Michael A; Ditzel, Ricky M; Cap, Andrew P
ABSTRACT: Introduction: Hypocalcemia is a known sequela of citrated blood product transfusion. Civilian data suggest hypocalcemia on hospital admission is associated with worse outcomes. Initial calcium levels in military casualties have not previously been analyzed. The objective of this retrospective review aimed to assess the initial calcium levels in military trauma casualties at different Forward Surgical Teams (FST) locations in Afghanistan and describe the effects of prehospital blood product administration on arrival calcium levels. Materials and Methods: This is a retrospective cohort analysis of military casualties arriving from point of injury to one of two FSTs in Afghanistan from August 2018 to February 2019 split into four locations. The primary outcome was incidence of hypocalcemia (ionized calcium < 1.20 mmol/L). Results: There were 101 patients included; 55 (54.5%) experienced hypocalcemia on arrival to the FST with a mean calcium of 1.16 mmol/L (95% confidence interval [CI], 1.14 to 1.18). The predominant mechanism of injury consisted of blast patterns, 46 (45.5%), which conferred an increased risk of hypocalcemia compared to all other patterns of injury (odds ratio = 2.42, P  = .042). Thirty-eight (37.6%) patients required blood product transfusion. Thirty-three (86.8%) of the patients requiring blood product transfusion were hypocalcemic on arrival. Mean initial calcium of patients receiving blood product was 1.13 mmol/L (95% CI, 1.08 to 1.18), which was significantly lower than those who did not require transfusion ( P  = .01). Eight (7.9%) of the patients received blood products before arrival, with 6/8 (75%) presenting with hypocalcemia. Conclusions: Hypocalcemia develops rapidly in military casualties and is prevalent on admission even before transfusion of citrated blood products. Blast injuries may confer an increased risk of developing hypocalcemia. This data support earlier use of calcium supplementation during resuscitation.